Pembinaan Desain Produk Amplang Ikan sebagai Alternatif Usaha Rumahan bagi Ibu-Ibu PKK Desa Terantang, Barito Kuala - Rizky Nastiti; Norbaiti Norbaiti; Masithah Akbar; Lydia Goenadhi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Terantang Village is located in Barito Kuala Regency, where the women are members of the PKK, which is where they learn to start a home business. Most PKK members are housewives who have just started small businesses such as spinach chips. This training aimed to provide the participants with a business alternative, from determining and designing products that suit their conditions to training on how to produce these products. Fish amplang was offered as an alternative product, considering that the raw material in the form of fish is easy to obtain and does not require special equipment in its manufacture. This activity is carried out by providing material about product design and practicing making fish amplang taught by an amplang business owner. From the activities carried out, the participants gained new skills regarding the design of fish amplang products. In addition, this training is expected to be a provision for them to develop their businesses. Furthermore, from the evaluation results, it is found that the participants are satisfied with the training carried out, especially since they can learn new skills. They also request that similar training be held periodically.